Disabled People, Work and Welfare Is Employment Really the Answer? - Grover, Chris; Piggott, Linda (2015)
This is the first book to challenge the concept of paid work for disabled people as a means to 'independence' and 'self determination'. Recent attempts in many countries to increase the employment rates of disabled people have actually led to an erosion of financial support for many workless disabled people and their increasing stigmatisation as 'scroungers'. Led by the disability movement's concern with the employment choices faced by disabled people, this controversial book uses sociological and philosophical approaches, as well as international examples, to critically engage with possible alternatives to paid work. Essential reading for students, practitioners, activists and anyone interested in relationships between work, welfare and disability.